STUDENTS’ PERCEPTIONS OF DISCORD AS A LEARNING TOOL IN EFL CLASSROOM - Wijaya, Nata Kesuma (English Edu: Journal of English Teaching and Learning, 2023)
Firstly introduced in 2015, Discord has been widely used as a social media platform amongst worldwide gamers to effectively assist them to communicate with each other. As a learning management system (LMS), it offers more advantageous yet economical full features. Referring to previous studies, this research found the main general lack: most of the studies focused only on elementary schools and universities. As a result, this research will reveal Discord as a learning media focusing on the 11th grade Islamic senior high school students to capture students’ perspectives toward the perceived usefulness (PU) and perceived ease of use (PEOU) of Discord. This study uses a mixed research methodology. In addition, a cross-sectional survey design is used to gather data at a point of time. It is applied as a cross-sectional survey design can be used to examine current attitudes, beliefs, opinions, or practices. This study picked a total of 31 (thirty one) samples to be involved. For quantitative, questionnaire guidance is used to measure the perceived usefulness (PU) and perceived ease of use (PEOU) of Discord in general. For qualitative, interview guidance is used to assist in interviewing several samples to dig deeper into students’ perspectives toward Discord. From the analysis, Discord is proven containing perceived usefulness (PU) and perceived ease of use (PEOU) based on the questionnaire and interview results. However, this research has several lacks regarding the research process and content. Therefore, for further research, this research suggests using statistical data showing actual improvement in English mastery as well as students’ perspectives toward Discord as a learning media.